Legitimacy crises in Pakistan (A comparative study of political behavior) - Dr. Mughees Ahmed (Journal of Political Studies, 2007)
This paper presents a thorough review of legality of governments in Pakistan. It suggests that how non-political rulers have legalized their authority within the political system of Pakistan. This paper analyses the behavior of dictators and their supporters and even opponents which legitimize unconstitutional actions taken by dictators. Analytical and political interaction approach is adopted in this paper. Another object of this discussion is to analyze the behavior of politicians and the judiciary about the legitimacy of dictators’ rule.